Pengembangan LKPD Materi Inovasi Teknologi Biologi Melalui Kajian Pengaruh Penambahan Kayu Manis Dan Jenis Gula Terhadap Kualitas Water Kefir Nanas (Ananas Comosus (L.) Merr.) - Azizah Safitri; Zulfarina; Imam Mahadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to develop a Student Worksheet (LKPD) design for the topic of Biological Technology Innovation in Grade X of Senior High School through the enrichment of functional beverage production in the form of water kefir made from pineapple (Ananas comosus (L.) Merr.) with the addition of cinnamon and different types of sugar. The research was conducted from October 2024 to February 2025 at the Biology Education Laboratory, University of Riau. The method used was an experimental approach with a completely randomized design (CRD) in a factorial pattern consisting of two factors: types of sugar (granulated sugar and palm sugar) and cinnamon concentration (0%, 1%, and 3%), with each treatment replicated three times. The observed parameters included organoleptic and hedonic tests. The results showed that the best combination was found in the treatment using palm sugar and 10 grams of cinnamon (G2K1). This water kefir was preferred by the panelists due to its mild sourness and a balanced aroma of fermentation and cinnamon. The findings of this study were subsequently integrated into the LKPD design and validated by subject matter and media experts, indicating its feasibility as an instructional material for biotechnology learning in high school.